Avaliação do desempenho, da formação de depósitos e da composição da microbiota em um reator anaeróbio com membranas (AnMBR) tratando esgoto sanitário - Agostini, Rodolfo dos Santos de (2023)
Anaerobic membrane reactors (AnMBR) have gained prominence in the in recent years, mainly due to its ability to decouple the time of detention hydraulic retention time of the cell, allowing for the slow growth of the anaerobic microorganisms, the adoption of high organic loads, and the obtaining quality effluents with good methane productivity. One of the The main limiting factors of AnMBR reactors is the formation of deposits in the membranes (fouling), which is associated with a complex interaction of factors biological, physical and chemical effects that occur in reactors, affecting in a transmembrane pressure and permeate flow are important. The Present The objective of this study is to evaluate the performance of an AnMBR by treating sanitary effluent on a pilot scale and characterize the physical fouling layer and microbiologically. This work was divided into three articles. In the first article the treatment efficiency of the AnMBR reactor was evaluated in comparison to a UASB reactor, treating the same sanitary effluent. The AnMBR reactor featured greater efficiency in the removal of organic matter, solids and pathogens, with COD removal efficiencies of 87.1 ± 8.1%, OSH of 95 ± 5%, and 106 E. coli In the second article, the characterization of the fouling. An important influence of the cake layer on the reduction was observed of the permeability of the membranes, accounting for 80.1% of the resistance to filtration. The results point to a role of biopolymers in the fouling formation process in membranes. In the third article, the microbiological characterization of the mixed liquor of the reactor and the fouling layer. Great microbiological diversity was observed in the reactor, highlighting a nucleus of microorganisms formed by the Deltaproteobacteria classes, Clostridia, Bacteroidia and Epsilonproteobacteria, which correspond to 51.94% of the identified microorganisms. A great similarity was also found between the microorganisms present in the mixed liquor and in the cake layer, however Great differentiation in relation to membrane-adhered microorganisms After physical removal of the cake layer, 15 genera of microorganisms exclusively in this sample.